Quenching effect of uranyl species in the photoluminescence emission and visible-light-driven water dissociation activity of CdS and TiO2 photocatalysts - Gupta, Narendra M.; Kelkar, Sarika A.; Korake, Prakash V. (Photochemical & Photobiological Sciences, 2016)
Anchoring of uranyl species (2-4 mol%) led to the complete quenching of photoluminescence emission and the visible-light-driven water photodissociation activity of TiO2 (Degussa-P25) and a hydrothermally synthesized CdS photocatalyst. Photophysical measurements revealed a fast relaxation and the transfer of photogenerated electrons/energy from the TiO2 or CdS substrate to the acceptor uranyl moieties. Besides the position of flat band levels, significant overlap of the absorption/emission spectra of the host matrix and the surface-bound UO22+ species is responsible for this reverse energy transfer from a wide bandgap semiconductor to a material with a smaller band-to-band energy gap.